The effect of different levels of garlic extract administration at various time periods on the extent of serumic lipid peroxidation in laying hens - saeed rasoulinejad; nariman sheykhi; hossein hassanpour (Āsīb/shināsī-i Darmāngāhī-i Dāmpizishkī, 2013)
Free radicals are involved in molecular changes and mutation and if they are not inactivated the resultant lipid peroxidation will damage all types of cellular macromolecules such as proteins, carbohydrates, lipids and nucleic acids. Natural diet containing antioxidants plays an important role in health, reproduction, performance, safety and growth in poultry. Garlic extract with a high antioxidant effect very useful against free radicals and infective agents. In this study, the effect of concentration of 0.01 and 0.02% of garlic extract in drinking water with periods of 2, 4 and 6 days a week were evaluated on lipid peroxidation. In addition to assessing the best concentration, economic aspects were also considered. So at the end of the third week, the best effect on reducing lipid peroxidation was seen in T3 which had received the concentration of 0.02% of garlic extract, two days a week.  After six weeks of trial, Group T7 which had received the concentration of 0.02% garlic extract for 6 days a week, showed the best effect on reducing lipid peroxidation. Our studies also showed that garlic extract improved mass production in all groups compared to the control group.  Considering the amount of lipid peroxidation at the end of the sixth week, herd performance in six weeks and calculating the average sale price of mass production, minus the cost of feed consumed per group, it is concluded that group T4 which received garlic extract concentration of 0.01% for 4 days a week (Saturday, Monday, Wednesday, Thursday) showed the best option in view of the economic conditions.